2013
DOI: 10.1523/jneurosci.1510-13.2013
|View full text |Cite
|
Sign up to set email alerts
|

Zebrafish Embryonic Neurons Transport Messenger RNA to Axons and Growth ConesIn Vivo

Abstract: Although mRNA was once thought to be excluded from the axonal compartment, the existence of protein synthesis in growing or regenerating axons in culture is now generally accepted. However, its extent and functional importance remain a subject of intense investigation. Furthermore, unambiguous evidence of mRNA axonal transport and local translation in vivo, in the context of a whole developing organism is still lacking. Here, we provide direct evidence of the presence of mRNAs of the tubb5, nefma, and stmnb2 g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
30
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(33 citation statements)
references
References 49 publications
2
30
0
1
Order By: Relevance
“…3). In agreement with previously observed localisation of mRNA (Baraban et al, 2013), newly synthesised protein frequently accumulated in the axon initial segment (arrowheads in Fig. 3A,B,G,H).…”
Section: Protein Synthesis In Axonssupporting
confidence: 92%
See 3 more Smart Citations
“…3). In agreement with previously observed localisation of mRNA (Baraban et al, 2013), newly synthesised protein frequently accumulated in the axon initial segment (arrowheads in Fig. 3A,B,G,H).…”
Section: Protein Synthesis In Axonssupporting
confidence: 92%
“…The TimeStamp cassette comprising the NS3 domain of the hepatitis C virus (HCV) polyprotein, flanked by its NS4A/B specific cleavage sites and followed by an HA epitope coding sequence was obtained from the PSD95 plasmid (Lin et al, 2008). It was cloned in frame with Venus coding sequence in plasmid 5xUAS:myrVenus_3'UTR_chicken_ß-actin (Baraban et al, 2013). Chicken ßactin-∆Zipcode and zebrafish tubulin-ß5 and neuroD 3'UTR sequences as described in (Baraban et al, 2013) were substituted to the original chicken ß-actin 3'UTR to obtain the corresponding plasmids.…”
Section: Cloning Of the Spot Translation Reporter Constructsmentioning
confidence: 99%
See 2 more Smart Citations
“…Combining clemizole with HCV protease inhibitors proved to be highly synergistic, strongly enhancing the potency of such therapeutics (Einav et al, 2010). Moreover, a recent study of Baraban et al (2013) reported that clemizole inhibits spontaneous seizures in a zebrafish model for Dravet syndrome (scn1Lab mutant), a rare and severe form of monogenic epilepsy, which is mainly caused by mutations in Nav1.1 (SCN1A), a voltage-gated sodium channel (Catterall, 2014). However, high concentrations of 100 mM clemizole were needed to suppress spontaneous hyperactivity.…”
Section: Discussionmentioning
confidence: 99%